A Prospective Study of Dermoscopic and Ultrastructural Features of Vitiligo-Associated Leukotrichia - Li M; Wang F; Li X; Ding X; Du J (Dove Medical Press, 2023)
Man Li,* Fang Wang,* Xinxin Li, Xiaolan Ding, Juan Du Department of Dermatology, Peking University People's Hospital, Beijing, 100044, People's Republic of China*These authors contributed equally to this workCorrespondence: Fang Wang; Juan Du, Department of Dermatology, Peking University People's Hospital, No. 11 Xizhimen South Street, Xicheng District, Beijing, 100044, People's Republic of China, Fax +861088325474, Email wfangxixi@sina.com; dujuan223@126.comBackground: Dermoscopic and ultrastructural features of vitiligo-associated leukotrichia (VAL) have not been well studied. This study is aimed at the dermoscopic and ultrastructural features of VAL.Methods: We present a cross-sectional study of VAL-related dermoscopic signs and their relationship with disease stages and duration of leukotrichia. Characteristics of hair surface and finer details including melanosomes, macrofibrils, and remnant nucleus were observed under Electron Microscopy (EM).Results: One hundred and forty samples on distinct sites from 100 patients were collected. Among 75 VAL from the scalp, the prevalence of diameter diversity of leukotrichia (52.6% vs 8.1%), Pohl-Pinkus constrictions (34.2% vs 0), and depigmented hair roots signs (34.2% vs 8.1%) in patients with progressive vitiligo was much higher than that in patients with stable vitiligo (all P< 0.05). The EM result of VAL showed that melanosomes were smaller with vesicles formation, reduced counts, and incomplete shape, and macrofibrils were irregularly arranged with widened spaces and vesicles formation.Limitations: No conclusions about the histopathologic characteristics or dermoscopic-histopathologic correlation of the VAL.Conclusion: The dermoscopic signs of diameter diversity of leukotrichia, Pohl-Pinkus constrictions, and depigmented hair roots are related to progressive vitiligo. The process of melanin synthesis and formation of VAL are impaired at the early stage of VAL under Electron microscopy.Keywords: vitiligo, leukotrichia, dermoscopy, electron microscopy, diameter diversity, Pohl-Pinkus constrictions, melanosomes